The Effect of Geoquarium Magic Educational Game Tool on The Ability to Recognize Geometry Shapes in Children 4-5 Years Old - Jhoni Warmansyah; Rahayu Nola,Sari; Eliza Febriyani; Azizahtil Mardiah; Alfira Marfiyenti (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2022)
This study aims to determine the effect of the educational game tool (ape) geoquarium magic on the ability to recognize geometric shapes in children aged 4-5 years. This study uses an experimental method with a pre-experimental design and the type of one-group pre-test-posttest design. The research sample comprised 12 children using a simple randomized technique. The data collection techniques used observation sheets. Then the data analysis technique used the statistical technique of t-test (t-test). The results got from the application of the geoaquarium magic educational game tool showed that the ability to recognize geometric shapes in children increased after being given treatment, as evidenced by the t count greater than the t table with an alpha significance level of 0.05. Thus, teachers can use these educational game tools as a strategy to develop the ability to recognize from an early age. To overcome the low ability of children in recognizing geometric shapes from an early age, further action research can be carried out.